Carcass yield and health status of broilers fed aflatoxin B1 diets added with Mycosorb - Nalle, Catootjie Lusje; Supit, Max Arthur Julian; Angi, Andrijanto Hauferson; Bha, Beatrix Se-na; Yuliani, Ni Sri (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The intake of aflatoxin B1 (AFB1) can lead to poor productivity and diseases in birds. Thus, it is important to minimize the toxic effects of AFB1. The objective of this study was to evaluate the carcass yield and haematological profile of broilers fed diets containing AFB1 added with Mycosorb. A total of 240-day old broiler chicks were randomly distributed to 24 pens (10 birds/pen). The experiment was designed using a 4 x 2 factorial arrangement with two different factors, namely aflatoxin level and Mycosorb. The treatments were control diets, control diets added with Mycosorb, diets containing 10.36 ppb AFB1, diets containing 10.36 ppb AFB1 added with Mycosorb, diets containing 26.97 ppb AFB1, diets containing 26.97 ppb AFB1 added with Mycosorb, diets containing 61.06 ppb AFB1, diets containing 61.06 ppb AFB1 added with Mycosorb. There was an interaction (p<0.05 to 0.01) between AFB1 level and Mycosorb on the white blood cells (WBC) and litter/excreta score (LES), but not (p>0.05) in tcarcass traits (CT), lymphoid organ weight (LOW), and haematological profile (HP) of broilers. Level of AFB1 did not affect (p>0.05) all CT, LOW, and HP, but it affected (p<0.001) the LES. Mycosorb did not improve (p>0.05) CT, LOW and HP of broilers.Â  In conclusions, 1) dietary Mycosorb in afla-treated diets improved litter quality and reduced white blood cell counts of broilers; 2) the AFB1 level up to 61.06 ppb did not impair carcass yield, lymphoid organ weights and other haematological index of broilers.